Scenes of Indifference : The Addressee of the Adventure - Alice Lagaay and Malte Fabian Rauch (Etica & politica, 2020)
The article, born of a dialogue between two thinkers of negativity and the neuter, elaborates Agamben’s philosophy of indifference through a series of (dis)connected scenes or thematic episodes. These scenes do not so much describe as perform indifference, insofar as they pursue the same themes through in-different variations. In seeking to critically articulate Agamben’s ‘archaeology of the subject’ by assessing the manner in which Agamben’s thought picks up and differs from Foucault and Heidegger as well as the lesser known Salomo Friedlaender/Mynona, the text evokes a range of avenues into deactivation, inoperativity, indifference, and the event. The deliberately performative approach both addresses and seeks to embody the spirit of adventure at work in Agamben’s thinking by exploring a plane and practice of thought “below” or beyond surface assumptions of identity and position –where ways of being, forms of life, and modes of thinking and writing attune, and are acquiesced to, as necessarily open and plural. The essay seeks to show how Agamben’s attempts to render inoperative the metaphysical determinations of the human as subject are keyed to a specific form of address, an address that can be understood as a response to Jean-Luc Nancy’s question “who comes after the subject”?
Keywords: Active/Passive; Aesthetics of Existence; Subjectivity; Anthropogenesis; Creative Indifference; Deactivation; Inoperativity; Event; Form of Life; Freedom; Ways of Being